Penerapan Pembelajaran Berdiferensiasi Untuk Meningkatkan Hasil Belajar Peserta Kelas IV SDN 112 Palembang - kurnia suci bransa Suci; Siti Dewi Maharani; Vinencia Ika Indralin (Universitas Sriwijaya in Collaboration with HDPGSDI (Himpunan Dosen PGSD Indonesia), 2024)
Research in this regard wants to know the application of differential learning can improve the learning outcomes of pupils of the fourth grade of the State Basic School 112 Palembang. This type of research is class action research with two cycles. Using data gathering techniques for test learning results. Based on the results of the study, the student's results at the pre-cycle reached a degree there were 14 pupils with a presentation of 46.66%. Cycle I, there were 22 pupils have a degree of presentation of 73.33%. In the II cycle, the pupils reached the degree of 28 pupils and presentations of 9.33%. Then the application of differential learning was concluded, on the subjects of IPAS class IVA the topic “Energy Transformation” can improve the learning results of pupils.